2019
DOI: 10.15390/eb.2019.7819
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family Participation in Nutrition Education Intervention on the Nutritional Status of Preschool Age Children

Abstract: Okul öncesi dönemdeki çocukların beslenme durumuna yönelik beslenme eğitimine, aile katılımının etkinliğini değerlendirmek için bir devlet anaokuluna giden 74 çocuğa 10 haftalık bir beslenme eğitimi programı uygulanmıştır. Çocuklar, aile katılım grubu (AKG), eğitim grubu (EG) ve kontrol grubu (KG) olmak üzere üç gruba ayrılmıştır. Müdahaleler; okul temelli beslenme eğitimi, aile beslenme eğitimi dokümanları ve aile-çocuk ev etkinlikleri ile aylık aileler ile toplantılar AKG'de, okul temelli beslenme eğitimi EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Diversos estudios avalan esta recomendación, identificando al entorno familiar como un potencial factor de mejoría del estado nutricional de los niños y de la conducta sedentaria 18 . Además, la participación de la familia puede aumentar la efectividad de la educación nutricional mediante la disponibilidad, oferta y patrones de consumo 19,20 .…”
Section: Estado Nutricionalunclassified
“…Diversos estudios avalan esta recomendación, identificando al entorno familiar como un potencial factor de mejoría del estado nutricional de los niños y de la conducta sedentaria 18 . Además, la participación de la familia puede aumentar la efectividad de la educación nutricional mediante la disponibilidad, oferta y patrones de consumo 19,20 .…”
Section: Estado Nutricionalunclassified
“…Previous multicomponent intervention studies that have reported positive effects on dietary intake were conducted over a longer timeframe ranging from ten weeks (56) to one year (15,29,30) . Either a delayed post-intervention assessment or repeating the intervention for an extended period, to provide greater time for changes in the home food environment (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various factors such as parents' feeding behavior, parenting practices, eating environment at home, and socioeconomic status can affect children's feeding behavior (Stage et al, 2018). It is stated that ensuring family participation in preschool nutrition education programs is effective in improving the knowledge and awareness of families as well as developing positive feeding behavior in children (Aktaç, Kızıltan, & Avcı, 2019). However, since there was no significant increase in the eating awareness of the mothers in our study, it is an expected result that there was no significant improvement in child feeding behavior.…”
Section: Pediatric Feeding Behavior Based On the Reports Of Mothersmentioning
confidence: 99%